2015
DOI: 10.1177/0731684415617247
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of interface delamination in composite T-joint using couplant-free Lamb wave methods

Abstract: Need for quick NDE methods during field maintenance of aircraft has become a focus of attention due to increase in use of co-cured skin-stiffened composite structures. When Lamb wave propagates over skin-stiffened structures, the occurrence of multiple modes is unavoidable due to structural features such as stringers and stiffeners, which in turn makes the interpretation of received wave difficult and limits the defect-detection ability of Lamb waves. Using finite element simulations, propagation of incident S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The conventional methods pose drawbacks like point-by-point inspection and time-consuming to inspect larger areas. 2,12 Ultrasonic guided wave techniques have been widely used in recent years due to their reliable, rapid and wide range detection advantages. 2,13,14 Guided wave inspection of bonded elastic-viscoelastic multilayered structures, frequency and mode selection are well described elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional methods pose drawbacks like point-by-point inspection and time-consuming to inspect larger areas. 2,12 Ultrasonic guided wave techniques have been widely used in recent years due to their reliable, rapid and wide range detection advantages. 2,13,14 Guided wave inspection of bonded elastic-viscoelastic multilayered structures, frequency and mode selection are well described elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional methods pose drawbacks like point-by-point inspection and time-consuming to inspect larger areas. 2,12…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, studies on the interaction of Lamb waves with delamination-type defects have been reported by many researchers in composite laminates. 59…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, studies on the interaction of Lamb waves with delamination-type defects have been reported by many researchers in composite laminates. [5][6][7][8][9] Of the various transduction methods available, aircoupled ultrasonic testing (AUT) technique is emerging as a promising method for non-contact inspection of composites. 7,[10][11][12] The advantages of AUT include rapid automated scanning, excitation of a pure Lamb wave mode 11,13 and inspection of irregular and inaccessible regions.…”
Section: Introductionmentioning
confidence: 99%